Korea : Financial Sector Assessment - World Bank (World Bank, Washington, DC, 2013)
Since the financial crisis in 1997-98, Korea has made major progress in financial, and corporate sector reform - the supervisory and regulatory regime for the financial sector has been substantially strengthened, and recent reforms helped achieve a high degree of observance of international standards, and codes. Moreover, significant consolidation in the banking system took place, with banks becoming more profit oriented, and their operations streamlined. The impressive macroeconomic performance led to strong real growth, low inflation, and growing official foreign reserves, facilitating the improvement of measured financial sector soundness. However, important reform measures were delayed, e.g., addressing issues in the areas of insurance and securities, adopting the insolvency framework, and in the completion of corporate restructuring, reforms crucial to prevent an economic downturn. Despite progress in prudential supervision, concerns remain on the regulator's ability to supervise risks, and, information and monitoring of connected lending and cross ownership in the financial crisis, also remain issues of concern. Key recommendations suggest that steps should be taken to reassure markets that the independence of the regulator is important; that measures to strengthen provisioning for household lending are welcome; that a full examination of the Korea Development Bank should be conducted, including a review of the derivatives-related accounting systems, complemented by a targeted external audit of the bank; a continued pension reform is urgent given the rapidly aging population; and, particularly worrisome is the seemingly inadequate supervision of the problems arising from non-bank deposits taking institutions' face soundness, where tighter supervision of securities is warranted. Similarly, corporate governance and disclosure need further steps, aligning accounting and auditing reforms with evolving internal best practices.